Marine microorganisms as an untapped source of bioactive compounds - Ameen, Fuad (Saudi J Biol Sci, 2021)
The search for novel biologically active molecules has extended to the screening of organisms associated with less explored environments. In this sense, Oceans, which cover nearly the 67% of the globe, are interesting ecosystems characterized by a high biodiversity that is worth being explored. As such, marine microorganisms are highly interesting as promising sources of new bioactive compounds of potential value to humans. Some of these microorganisms are able to survive in extreme marine environments and, as a result, they produce complex molecules with unique biological interesting properties for a wide variety of industrial and biotechnological applications. Thus, different marine microorganisms (fungi, myxomycetes, bacteria, and microalgae) producing compounds with antioxidant, antibacterial, apoptotic, antitumoral and antiviral activities have been already isolated. This review compiles and discusses the discovery of bioactive molecules from marine microorganisms reported from 2018 onwards. Moreover, it highlights the huge potential of marine microorganisms for obtaining highly valuable bioactive compounds.